The Effect of COVID-19 on Blood Pressure Control in Hypertension Patients– A Literature Review - Raditya Manusakti; Judya Sukmana; Wachjudi Kurniaj; Liliawanti (Institute of Medico-legal Publications Pvt Ltd, 2021)
COVID-19 is caused by Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2). First identifiedin Wuhan, China, in December 2019, and declared an International Public Health Emergency in January2020, the WHO declared a pandemic in March 2020. Hypertension, a disease that has long been a problemfor most people in Indonesia and around the world . COVID-19 can affect blood pressure control for peoplewith hypertension due to obstruction of the RAAS system. This research was conducted to find out whateffect COVID-19 has on blood pressure control in people with hypertension. In the condition of COVID-19patients with comorbid hypertension, SARS-CoV-2 which attacks ACE2 can eliminate the role of ACE2 inthe RAAS system. Inhibition of ACE2 can also cause buildup of angiotensin II which has a vasoconstrictiveeffect. This results in the absence of homeostasis in the blood pressure control system and makes bloodpressure conditions that continue to be at high pressure.